Mortgage Choice Determinants: The Role of Risk and Bank Regulation1. Issue 295 (14th July 2015) - Dungey, Mardi; Doko Tchatoka, Firmin; Wells, Graeme; Yanotti, María B.
Abstract : We shed new light on the role of borrower characteristics in mortgage product choice, and how these are impacted by regulatory capital requirements. Using rich loan‐level data from the Australian market, we analyse the borrower idiosyncratic risk effects on the choice between variable‐rate mortgages and other mortgages with reduced initial payments. We find that income, wealth and mobility risks play a role in product choice. We investigate regulatory capital requirements in a market where banks hold mortgage risk on balance sheet and find that the Basel capital discounts based on loan‐to‐valee ratios divide otherwise similar borrowers in their mortgage choices.